The TestIdeals package for Macaulay2 - Erin Bela; Alberto F. Boix; Juliette Bruce; Drew Ellingson; Daniel Hernández; Zhibek Kadyrsizova; Mordechai Katzman; Sara Malec; Marcus Robinson; Karl Schwede; Daniel Smolkin; Pedro Teixeira; et al. (The Journal of Software for Algebra and Geometry, 2019)
We describe a Macaulay2 package for computations in prime characteristic commutative algebra. This includes those for Frobenius powers and roots, p−e-linear and p e-linear maps, singularities defined in terms of these maps, different types of test ideals and modules, and ideals compatible with a given p−e-linear map
Keywords: TestIdeals package; Macaulay2; Frobenius powers; Frobenius roots; test ideals; F-singularities; prime characteristic algebra; type of access: open access